A preliminary investigation of parent-reported fiction versus non-fiction book preferences of school-age children with autism spectrum disorder. (October 2018) - Davidson, Meghan M; Ellis Weismer, Susan
Background & aims: Anecdotal evidence suggests that individuals with autism spectrum disorder prefer non-fiction books over fiction books. The current study was the first to investigate parent-reports of children with autism spectrum disorder's fiction and non-fiction book preferences and whether these relate to individual differences in social communication, oral language, and/or reading abilities. Method: Children (ages 8–14 years, M = 10.89, SD = 1.17) with autism spectrum disorder diagnoses ( n = 19) and typically developing peers ( n = 21) participated. Children completed standardized measures of social communication, oral language, and reading abilities. Parents reported children's current favorite book, and from these responses, we coded children's fiction versus non-fiction book preferences. Main contribution: Contrary to anecdotal evidence, children with autism spectrum disorder preferred fiction similar to their typically developing peers. Fiction versus non-fiction book preference was significantly related to social communication abilities across both groups. Children's oral language and reading abilities were related, as expected, but the evidence for a relationship between social communication and reading comprehension was mixed. Conclusions: This study provides preliminary evidence supporting the association of social communication in fiction versus non-fiction book preference, which may be related to children's comprehension and support the theoretical role of social communication knowledge in narrative/fiction. Implications: It should not be assumed that all children with autism spectrum disorder prefer expository/non-fiction or do not read narrative/fiction. Children who prefer non-fiction may need additional social communication knowledge support to improve their understanding of narrative fiction.